INTEGRATION OF CLOUD COMPUTING ON MATHEMATICS TEACHING AND LEARNING IN PUBLIC UNIVERSITIES IN ENUGU STATE - Odoh, Cornelius Ekene; Onoh, David Onyemaechi; Ogbozor, Grace (Top Educational Review Journal (TERJ), 2024)
This study investigated the integration of cloud computing in mathematics teaching and learning in public universities in Enugu State. Cloud computing is an Internet-based facility that allows users to access shared computer applications, storage, and resources through a network of remote servers. Service users access the Internet using computers, laptops, or mobile phones. The research design adopted for this study is a descriptive survey research design. This study was carried out in Enugu State. Three research questions and one research hypothesis guided the study. A sample of 50 Mathematics education students and lecturers was used using a simple random sampling technique. Data were collected using a well-structured questionnaire. The reliability was done using Cronbach alpha reliability which was obtained as 0.87. Mean and standard deviation were used to answer the research questions. This study adopted a survey design. The findings reveal that the integration of clouds in mathematics education significantly impacts cost-effectiveness, enhanced availability, increased operability, and so on. The study recommends that computing power provided by the cloud allows students to extend mathematics learning beyond the walls of the classroom, thereby offering the learner’s participation and control of the learning process